Mangupa-upa Sebagai Sarana Untuk Membrikan Ungkapan Doa,Syukur, dan Harapan dalam Tradisi Masyarakat Batak Angkola di Kec. Padang Bolak. Kab. Padang Lawas Utara - Sarifa Yuliani Siregar (LPPM Politeknik Pratama, 2024)
This research discusses the habits of the Batak people in the mangupa-upa tradition as an expression of gratitude, prayer, hope and joy, such as in marriage, getting achievements, getting a job, people just recovering from illness and even people who want to go on the Hajj. The tradition of forgetting is a tradition that is still carried out by the Batak people, especially the Angkola Batak people. This research aims to find out the mangupa-upa tradition and also the values contained in the mangupa-upa event in the customs of the Angkola Batak Tribe in North Padang Lawas Regency. This type of research is qualitative research with ethnographic methods. This research technique is interviews, observation and data collection. The results of this research explain the value and meaning of the Batak Angkola community towards the mangupa-upa tradition as an expression of gratitude, prayer to the Almighty God and as giving gifts to those they receive. The mangupa tradition in North Padang Lawas, especially at weddings, is ensured to be carried out at every wedding according to the Batak Angkola tradition. Apart from marriage, these wages are given to people who excel and get work. Apart from that, it is also done when someone is sick, or someone who is going on the Hajj, but this is usually only to provide food or dishes or in the Batak language mangalehen mangan.